Ambidextrous organization and agility in big data era: The role of business process management systems. Issue 5 (3rd September 2018) - Rialti, Riccardo; Marzi, Giacomo; Silic, Mario; Ciappei, Cristiano
Abstract : Purpose: The purpose of this paper is to explore the effect of big data analytics-capable business process management systems (BDA-capable BPMS) on ambidextrous organizations' agility. In particular, how the functionalities of BDA-capable BPMS may improve organizational dynamism and reactiveness to challenges of Big Data era will be explored. Design/methodology/approach: A theoretical analysis of the potential of BDA-capable BPMS in increasing organizational agility, with particular attention to the ambidextrous organizations, has been performed. A conceptual framework was subsequently developed. Next, the proposed conceptual framework was applied in a real-world context. Findings: The research proposes a framework highlighting the importance of BDA-capable BPMS in increasing ambidextrous organizations' agility. Moreover, the authors apply the framework to the cases of consumer-goods companies that have included BDA in their processes management. Research limitations/implications: The principal limitations are linked to the need to validate quantitatively the proposed framework. Practical implications: The value of the proposed framework is related to its potential in helping managers to fully understand and exploit the potentiality of BDA-capable BPMS. Moreover, the implications show some guidelines to ease the implementation of such systems within ambidextrous organizations. Originality/value: The research offers a model to interpret the effects of BDA-capable BPMS on ambidextrous organizations' agility. In this way, the research addresses a significant gap by exploring the importance of information systems for ambidextrous organizations' agility.